Teaching Factory Learning Design for Vocational High Schools in Mechanical Engineering - Syamsul Bahri; Siraj Siraj; Wildan Zaqqi; Bagas Suanri (LPPM Universitas Malikussaleh, 2024)
The research aims to understand and analyze how the Teaching Factory model can be implemented in vocational high schools, particularly in the field of mechanical engineering. The type of research used is descriptive qualitative research. The research was conducted at Vocational High School in Lhokseumawe, which has already implemented the teaching factory model. Data collection in this study used three techniques: in-depth interviews, participant observation and documentation study. The data analysis technique used is the interactive model which includes: data reduction, data presentation, and conclusion drawing. Teaching Factory model implemented at Vocational High School in Lhokseumawe in the Mechanical Engineering expertise program has proven effective in improving students' competencies and preparing them for the workforce. The integration of theory and practice provided in this model greatly helps students master the skills needed in the industry. However, to maximize the potential of Teaching Factory, improvements in facilities, curriculum, and industry partnerships are needed. With the right improvements, Teaching Factory can continue to make significant contributions in producing skilled and employable workers.